Development of a new software for estimating credible interval of statistical indexes used for DNA evidence interpretation. Issue 1 (December 2019) - Manabe, Sho; Morimoto, Chie; Fujimoto, Shuntaro; Hirai, Eriko; Tamaki, Keiji
Abstract: There are several aspects of uncertainty that influence the strength of DNA evidence. Especially, the uncertainty of allele frequencies has a significant effect on the strength of DNA evidence. In this study, we developed a new software to estimate the credible interval of the strength of DNA evidence by considering the uncertainty of allele frequencies. This software considers the uncertainty based on the Dirichlet distribution in each locus, and estimates the credible intervals of random match probability, combined probability of inclusion, likelihood ratio for mixture interpretation by a binary model, and likelihood ratio for pairwise kinship analysis. In this article, we present an example of estimating a credible interval of the likelihood ratio in a simple mixture profile using the new software.